Desain Komunikasi Visual Berbasis Motion Graphic Interaktif untuk Kampanye Digital Anti-Perundungan di Sekolah - Rudjiono Rudjiono; Nining Fitriani; Muhammad Faiz Amrillah; Ahi Ritma Prianahatin (Pusat Riset dan Inovasi Nasional, 2025)
Bullying is one of the most common forms of violence still occurring in schools, causing serious impacts on students’ psychological conditions and social development. Various efforts have been made to reduce bullying cases, yet communicative campaign media that match the characteristics of the digital generation remain limited. This study aims to develop educational media based on interactive motion graphics designed with Visual Communication Design principles to support anti-bullying digital campaigns in schools. The research stages include designing the main characters using Adobe Illustrator and Adobe Photoshop, separating body parts in vector format for easier animation, importing the files into Adobe Character Animator, and synchronizing movements, facial expressions, and voices through dubbing processes. The final product is an interactive animation entitled “Berani Bicara, Berani Membela” (Dare to Speak, Dare to Defend), which features three main scenes: bullying in a school corridor, peer support in the classroom, and reporting the case to the guidance counselor. The findings indicate that this media provides a more engaging and interactive learning experience while effectively delivering moral messages. The animation not only emphasizes the importance of victims’ courage to report bullying but also highlights peer support and the school’s role in providing protection. Therefore, interactive motion graphics can serve as an alternative digital campaign strategy that is relevant, easily accepted by young generations, and has the potential to foster safe, inclusive, and friendly school environments for all students.